1996
DOI: 10.1152/ajpendo.1996.270.1.e91
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist inhibits endotoxin fever and systemic interleukin-6 induction in the rat

Abstract: Although a number of studies indicate that the pyrogenic activity of lipopolysaccharide (LPS) and/or interleukin (IL)-1 is mediated via induction of IL-6, this has been questioned by recent evidence demonstrating a dissociation between fever and circulating IL-6. The present study reexamines this relationship by use of human recombinant interleukin-1 receptor antagonist (IL-1ra). Injection of LPS (100 micrograms/kg ip) into rats induced fever (2.0 degrees C) that was significantly inhibited (P < 0.05) when IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(96 citation statements)
references
References 16 publications
9
85
0
2
Order By: Relevance
“…Consistent with this effect, systemic administration of recombinant IL-1␤ exacerbated ischemic damage and neurological deficit to a similar extent as LPS, suggesting that peripheral IL-1 challenge is a similar stimulus to LPS and further supporting that IL-1 is the key mediator of LPS in this brain injury paradigm. These results parallel previous studies showing that IL-1 is important for many host defense responses to systemic LPS challenge (Long et al, 1990;Luheshi et al, 1996;Miller et al, 1997b). It is likely that IL-1␤ was acting peripherally because levels were minimal in the circulation and undetectable in the brain after intraperitoneal administration (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with this effect, systemic administration of recombinant IL-1␤ exacerbated ischemic damage and neurological deficit to a similar extent as LPS, suggesting that peripheral IL-1 challenge is a similar stimulus to LPS and further supporting that IL-1 is the key mediator of LPS in this brain injury paradigm. These results parallel previous studies showing that IL-1 is important for many host defense responses to systemic LPS challenge (Long et al, 1990;Luheshi et al, 1996;Miller et al, 1997b). It is likely that IL-1␤ was acting peripherally because levels were minimal in the circulation and undetectable in the brain after intraperitoneal administration (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…IL-1 mediates several of the physiological and behavioral changes in response to a systemic inflammatory challenge induced by the bacterial endotoxin, lipopolysaccharide (LPS), or turpentine (Long et al, 1990;Luheshi et al, 1996Luheshi et al, , 1997Miller et al, 1997b). IL-1 may act by inducing the expression of an array of downstream mediators, several of which are pertinent to the systemic inflammatory response after stroke, in particular IL-6 and che-mokines (Miller et al, 1997b;Cartmell et al, 2000;Calkins et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 bioactivity in plasma was measured using B-9 hybridoma cells, essentially as described by Luheshi et al (1996). TNF bioactivity was measured by virtue of its cytolytic activity on actinomycin D-treated WEHI-164 cells over a period of 24 hr.…”
Section: Cytokine Bioassaysmentioning
confidence: 99%
“…Studies in experimental animals have demonstrated that recombinant IL-1␤, administered either systemically or directly into the brain, induces fever (2,17) and that neutralization of endogenous IL-1␤ attenuates fever (26,32,36). The majority of these neutralization studies were conducted with a recombinant form of the naturally occurring IL-1 receptor antagonist (IL-1ra) (37,52,64), which inhibits the action of IL-1 by competing for the IL-1 receptor (16). Like IL-1, this endogenous inhibitor is induced in the periphery after LPS challenge, and its levels increase in the circulation of febrile animals in parallel with IL-1␤ (3).…”
mentioning
confidence: 99%